Windows Server Hybrid Administrator Associate (AZ-800) Cert Prep: 2 Manage Windows Servers and Workloads in a Hybrid Environment. - Rahman, Seema (linkedin.com, 2022)
Learn how to manage Windows Servers and workloads in hybrid environments and prepare for the Microsoft AZ-800 exam.